High-resolution tumor marker detection based on microwave photonics demodulated dual wavelength fiber laser sensor - Jie Hu; Weihao Lin; Liyang Shao; Chenlong Xue; Fang Zhao; Dongrui Xiao; Yang Ran; Yue Meng; Panpan He; Zhiguang Yu; Jinna Chen; Perry Ping Shum (Opto-Electronic Advances)
The specific detection of tumor markers is crucial in early tumor screening and subsequent treatment processes. To accurately distinguish the signal response caused by trace markers, the high demodulation resolution of the sensor is necessary. In this paper, we propose a dual-wavelength fiber laser sensing system enhanced with microwave photonics demodulation technology to achieve high-resolution tumor marker detection. This sensing system can simultaneously perform spectral wavelength-domain and frequency-domain analyses. Experimental results demonstrate that this system's refractive index (RI) sensitivity reaches 1083 nm/RIU by wavelength analysis and –1902 GHz/RIU by frequency analysis, with ideal detection resolutions of 1.85×10–5 RIU and 5.26×10–8 RIU, respectively. Compared with traditional wavelength domain analysis, the demodulation resolution is improved by three orders of magnitude, based on the same sensing structure. To validate its biosensing performance, carcinoembryonic antigen-related cell adhesion molecule 5 (CEACAM5) is selected as the detection target. Experimental results show that the improved sensing system has a limit of detection (LOD) of 0.076 ng/mL and a detection resolution of 0.008 ng/mL. Experimental results obtained from human serum samples are consistent with clinical data, highlighting the strong clinical application potential of the proposed sensing system and analysis method.